Harnessing sovereign wealth funds in emerging economies toward sustainable development - El-Sholkamy, Mona Mostafa; Rahman, Mohammad Habibur (Cambridge : Cambridge University Press, 2022)
Sovereign Wealth Funds are government investment vehicles that have been present for decades. They are usually characterized by minimum information disclosure, however, this situation differed after worldwide events shed light on the role they possess to mitigate their downturns. The substantial economic influence they bring along due to their size and long term impact have recently created an uproar of debate that eventually led to the ratification of the Santiago Principles. The Principles set the stage for governing SWFs' operations and grant them more clarity. They also contribute to a more stable environment for cross-border investment flows. With the importance of SWFs, emerging economies also rose as key institutional investors; only this time they called for harnessing their funds towards sustainable development investment strategies. Despite pressuring need to improve transparency and governance structures of SWFs in EMs, the former are regarded as promising means for achieving the sustainable development goals.
Title from publisher's bibliographic system (viewed on 25 Jul 2022).
Keywords: Sovereign wealth funds; Sustainable development; Developing countries -- Economic conditions